Extraction and characterisation of maltene from virgin asphalt as a potential rejuvenating agent - Al-Saffar, Zaid Hazim; Yaacob, Haryati; Al Jawahery, Mohammed S.; Yousif, Salim T.; Mohd Satar, Mohd Khairul Idham; Putra Jaya, Ramadhansyah; Radeef, Hassanain Radhi; Eltwati, Ahmed Salama; Shaffie, Ekarizan (MDPI, 2023)
The wide application of reclaimed asphalt pavement (RAP) is hindered due to the highly brittle nature of the material, which contributes a major factor towards cracking-related distresses. While the utilisation of rejuvenating agents has been shown to enhance the flexibility of RAP, they also trigger certain negative effects on the performance of asphalt mixtures. In view of this, potential rejuvenators should be able to alter the rheological properties of asphalts to limit fatigue issues and enhance the potential of low-temperature cracking. Therefore, this study aimed to investigate the possibility of extraction and characterisation of maltene from virgin asphalt (VA) as a potential rejuvenating agent in RAP. Several physicochemical characteristics were examined, including density, viscosity, gas chromatography–mass spectrometry (GC–MS), Fourier-transform infrared (FTIR) spectroscopy, CHNS elemental analysis, and energy dispersive X-ray (EDX) analysis. Finally, the stiffness modulus characteristics of the different types of asphalt binders were evaluated at low and high temperatures. The results demonstrated that maltene was successfully extracted from VA using petroleum ether. In addition, the GC–MS showed that the extracted maltene contained polar and non-polar compounds with low molecular weights compared to VA. Furthermore, the spectra curve of maltene was very similar to that of asphalt, indicating its compatibility with asphalt binder and prospective use. Finally, adding maltene to aged asphalt decreased stiffness values to 0.0063, 0.0499, and 0.0108 MPa, which are equivalent to VA values (0.0061, 0.0481, and 0.0104 MPa) at loading times of 1.0, 0.1, and 0.55 s, respectively. Meanwhile, the stiffness modulus characteristics at low temperature were restored with the addition of maltene.